Improving critical thinking skills of high school students through learning mini research projects on household waste management activities - Rifka Haerani; Kusnadi Kusnadi; Taufik Rahman (Assimilation: Indonesian Journal of Biology Education, 2022)
This study explores the effect of mini research project learning on high school students critical thinking skills in household waste management activities. To achieve this goal, this study used a pre-experiment method with one group pre-test post-test design. Data were taken from first-grade students in one of the senior high schools in Bandung as research subjects for the experimental class without a control class. The test instrument (essay) adapted from Facione (2011) was used to measure students' critical thinking skills. The results showed that there was an increase in students' critical thinking skills after learning the mini research project with an average N-gain score of 0.55 (medium). The criteria for critical thinking skills had also changed from the average critical thinking score achievement which was very low (not manifested) to high (strong) which was seen based on the results of the initial and final tests.